Israelite religion and Biblical theology : collected essays - Miller, Patrick D. (Journal for the study of the Old Testament. Supplement series ;, 2000)
This is a formidable collection of previously published essays by this distinguished Old Testament scholar. Three significant areas of biblical studies have been a focus of the author's attention throughout his career: the Bible in its ancient Near Eastern world, the Psalms, and Old Testament theology. In Part I, epigraphic discoveries are examined for the light they shed on biblical texts. In Part II, special attention is given to the theological significance of reading the Psalms as a collection. In Part III, a wide range of theological issues-creation, covenant, prayer, cosmology, canon, an.